ANALYSIS OF CAUSES WHICH DETERMINE THE DEGRADATION OF CONVEYORS WITH METAL INSERTS - Sabin DIMULESCU; Dan DOBROTĂ (Fiabilitate şi Durabilitate)
The paper aims to analyze the causes that lead to the rapid degradation of the conveyor belts with metal inserts and their removal. Thus, the analysis revealed three main causes, namely the separation of the metal cord inserts from the rubber matrix, the longitudinal splicing of the conveyor belts with metal inserts, the appearance of micro cracks on the bearing face and on the rolling face. The analysis highlights the main aspects of the major problems encountered during the operation of conveyor belts.